2008
DOI: 10.12806/v7/i3/rf2
|View full text |Cite
|
Sign up to set email alerts
|

College Student Leaders: Meet the Alpha Female

Abstract: With the emergence of a new generation of strong and empowered female student leaders on college campuses, a special type of female leader, the Alpha Female, has developed. This study examines the essence of having an Alpha Female identity for 13 undergraduate women at a Midwestern university. Extensive interviews were conducted; transcripts were generated; emergent themes were derived; horizonalization and cross-case analysis was conducted; and, constant comparative method among the researches was employed. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…The results of the present study are consistent with previous research which has demonstrated that alpha females possess masculine traits [8, 10–13, 38]. It is also consistent with research that links these traits with leadership, strength and extroversion [11].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of the present study are consistent with previous research which has demonstrated that alpha females possess masculine traits [8, 10–13, 38]. It is also consistent with research that links these traits with leadership, strength and extroversion [11].…”
Section: Discussionsupporting
confidence: 92%
“…Research on the human alpha female has focused primarily on leadership [7, 8, 10–13, 88, 89]. In this research women who hold a leadership position in student and business organizations are labelled “alpha female”, a “special kind of leader” [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations